PENGARUH KARAKTERISTIK PEKERJAAN DAN KEPUASAN KERJA TERHADAP LOYALITAS KARYAWAN DI KOTA BANDAR LAMPUNG - Santika, Nyi Ayu; Efendi, Nur; Saptiani, Fenny (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2025)
This study aims to examine the influence of job characteristics and job satisfaction on employee loyalty. This research employs a quantitative approach with a descriptive research design. The sampling technique used was non-probability sampling with 100 private sector employees working in Bandar Lampung City as respondents. Data were collected through questionnaires distributed using a Likert scale. Data analysis in this study utilized multiple linear regression analysis with the assistance of SPSS 26. The findings indicate that job characteristics and job satisfaction collectively have a significant influence on employee loyalty in Bandar Lampung City.